More Pronounced Reduction of Gut Bacteria in Crohn's Disease than Ulcerative Colitis may have just Reflected Intimate Connection Rather than Difference of these two Diseases-A Different View on Findings Published in Gut - Xiaofa Qin (Archives of Clinical Gastroenterology - Peertechz Publications, 2017)
I read with great interest a paper published recently in Gut [1], as its fi nding that patients with Crohn's disease (CD) have more pronounced reduction and dysbiosis in gut bacteria than ulcerative colitis (UC) is just as what I have predicted during the last fi fteen years [2,3]. However, in contrast to the notion of the authors of the Gut paper that the more pronounced reduction in gut bacteria in CD suggests CD and UC are two different diseases, my prediction came from the perception of the profound intimate connections between UC and CD. As we know, countries and places have a high incidence of UC usually also have high rate of CD. However, it always showed a pattern that UC emerged fi rst, followed by CD, then CD showed a trend of catching up or even overpassing the incidence of UC. From my fi nding that digestive proteases such as trypsin and chymotrypsin can be inactivated by unconjugated bilirubin but not conjugated bilirubin and information gathered after that on infl ammatory bowel disease (IBD) including UC and CD, I  perceived that the primary cause for both UC and CD may be the impairment in the  inactivation of digestive proteases due to the reduction in gut bacteria, thus -glucuronidase enriched in certain kinds of gut bacteria that is needed for catalyzing the deconjugation of biliary bilirubin.